The mammalian secreted RNases: Mechanisms of action in host defence. Issue 1 (February 2013) - Gupta, Sandeep K; Haigh, Brendan J; Griffin, Frank J; Wheeler, Thomas T
The mammalian ribonucleaseA family comprises a large group of structurally similar proteins which are secreted by a range of tissues and immune cells. Their physiological role is unclear. It has been suggested that some of these RNases contribute to host defence, notably eosinophil-derived neurotoxin, eosinophil cationic protein, eosinophil-associated RNases, RNase4, angiogenin (RNase5), RNase7, RNase8 and bovine seminal RNase. This review summarises data supporting the involvement of these proteins in host defence, focusing on their antimicrobial, cytotoxic and immunomodulatory activities. The extent to which the data support possible mechanisms of action for these proteins is discussed. This compilation of findings and current hypotheses on the physiological role of these RNases will provide a stimulus for further research and development of ideas on the contribution of the RNases to host defence.